Tourism development and environmental degradation in the United States: evidence from wavelet-based analysis - Raza, Syed Ali; Sharif, Arshian; Wong, Wing Keung; Abd Karim, Mohd Zaini (Routledge, 2016)
The recent literatures indicate that the tourism development (TD) has significant influence over the environmental degradation of both high tourist-arrival and low-tourist-arrival countries. This study investigates the empirical influence of TD on environmental degradation in a high-tourist-arrival economy (i.e. United States), using the wavelet transform framework.This new methodology enables the decomposition of time-series at different time–frequencies.In this study, we have used maximal overlap discrete wavelet transform (MODWT), wavelet covariance, wavelet correlation, continuous wavelet power spectrum, wavelet coherence spectrum and wavelet-based Granger causality analysis to analyse the relationship between TD and CO2 emission in the United States by using the monthly data from the period of 1996(1) to 2015(3).Results indicate that TD is majorly having the positive influence over CE in short, medium and long run.We find the unidirectional influence of TD on CE in short run, medium and long run in the United States.